Content critical gaining competitive advantage through high-quality web content - McGovern, Gerry; Norton, Rob (Financial Times Prentice Hall, 2002)
The modern world runs on content. And the Web is fast becoming the medium of choice for content delivery. Increasingly business is about getting the right content to the right person at the right time ¿ and making a profit out of it. Content is critical. Content Critical will change the way you think about the Web. If part of your job involves writing original content to be placed on the Web ¿ product support material, a marketing pitch, or internal communication ¿ you¿re part of a publishing process. Think of your website as a publication and it all begins to make a lot of sense. Think of the person who visits your website as a reader and your objectives become clearer. Content Critical explains the theory and practice of producing reader-focussed, compelling content. It includes highly detailed, practical advice about what it takes to build a professional, content-oriented website, including classification, navigation, search and content layout. It shows you how to organize a publishing team and how to create a web publishing strategy.Discover what high-quality content really is, and learn how to create it.